Influence of temperature history on chloride diffusion in high volume fly ash concrete. (30th July 2017) - Jiang, Peng; Jiang, Linhua; Zha, Jie; Song, Zijian
Highlights: Different temperature histories were set to determine the chloride diffusion coefficient of HVFA concrete. Variations of chloride diffusion coefficient with temperature histories and age were revealed. Relationships between chloride diffusion coefficient with Maturity were obtained. Abstract: This paper presents the influence of temperature history on chloride diffusion of high volume fly ash (HVFA) concrete. Four different curing temperature histories, referenced as SDC (standard curing), SMC (steam curing), OC (outdoor curing) and TMC (massive concrete temperature matched curing), were set. Concretes with different replacement levels of fly ash were cast and cured under the four temperature histories, respectively. The variations of compressive strength, porosity and chloride diffusion coefficient with different ages were determined by experiment. SEM and XRD were used to analyze the microstructure and compositions of hydrated pastes. The results show that the performances of fly ash concrete were influenced by temperature histories. And the influence was more obvious with the addition of replacement level of fly ash. For ordinary concrete, higher accumulated temperature at early age got higher compressive strength, better pore structure and lower chloride diffusion coefficient, but had negative effects at later age compared to SDC. For HVFA concrete, it was beneficial for the development of performances. Although the chloride diffusion coefficient was higher than ordinary concrete at early age, it would become small even lower at later age. And higher accumulated temperature promoted this process. In addition, by utilizing the concept of maturity, good power function relations between chloride diffusion coefficient of fly ash concrete and Maturity were obtained at early age.